Bibliographical Review. Sáez, D., & Cabanelas, J. (1997). Cooperar para competir con éxito. Madrid: Ediciones Pirámide. - Kubus, Renata (Mercados y Negocios, 2022)
Cooperate to compete successfully is a short book in Spanish that provides a precise definition of cooperation between companies. The authors explain what cooperation entails and how companies can increase their competitiveness through cooperative ties. For the authors, cooperation is an intelligent response that aspires to increase competitiveness while facing changes.